Conditioning techniques and ischemic reperfusion injury in relation to on-pump cardiac surgery. (August 2014) - Holmberg, Fredrik Eric Olof; Ottas, Konstantin Alex; Andreasen, Charlotte; Perko, Mario J.; Møller, Christian H.; Engstrøm, Thomas; Steinbrüchel, Daniel A.
Abstract Objectives. The objective was to investigate the potential protective effects of two conditioning methods, on myocardial ischemic and reperfusion injury in relation to cardiac surgery. Design. Totally 68 patients were randomly assigned to either a control group (n = 23), a remote ischemic preconditioning (RIPC) group (n = 23) or a glucagon-like peptide-1 (GLP-1) analogue group (n = 22). The RIPC protocol consisted of three cycles of upper limb ischemia. The GLP-1 analogue protocol consisted of intravenous infusion with exenatide. The primary endpoint was postoperative cardiac enzyme release. The other secondary endpoints were metabolic parameters related to myocardial ischemia, measured using microdialysis technique, as well as other operative- and postoperative data. Results. Postoperative cardiac enzyme release indicated a possible beneficial effect of the interventions, but the difference did not reach statistical significance. RIPC showed a trend toward lower levels (p = 0.07). We managed to establish a functional myocardial microdialysis model, but we were unable to demonstrate clear protective effects. Conclusions. We were in this prospective randomized proof-of-concept trial, unable to show distinct protective effects of the studied conditioning methods. However, this trial can hopefully contribute to generate a productive discussion concerning limitations and future use of cardiac conditioning as well as microdialysis technique.